Diabetes und Soziales - Ebert, Oliver (Diabetologie und Stoffwechsel, 2018)
Diabetes mellitus is one of the most common chronic diseases at all ages. Diabetes and consequential damages can have a significant impact on the capability on affected people.Drug therapy resp. hypoglycemia can compromise the driving ability; problems in the choice of profession and in the daily work routine are possible.This paper aims to highlight said social implications and gives legal background information.
Keywords: Fahreignung; Fahrtüchtigkeit; Hypoglykämie; Schwerbehinderung; Berufsempfehlungen